TEACHING MATHEMATICAL DISCIPLINES AT THE MEDICAL UNIVERSITY - V. Ya. Gelman; L. A. Ushveridze; Yu. P. Serdyukov (Russian State Vocational Pedagogical University, 2018)
Introduction.In programs of training of students of medical specialties, Mathematics is a subject of basic education, i.e. non-core discipline. However, studying Mathematics is extremely important for future physicians, as recently there has been an impetuous development of mathematization in the field of health care. Today, a set of the new medical devices, the equipment and high technologies are being developed based on the mathematical modeling, analysis and forecasting. Mathematical methods are widely applied to diagnostics, development of life-support systems and the description of various biological processes both at the molecular level,  and at the level of a whole organism, its systems, bodies and tissues. The solution of many medical tasks in the field of taxonomy, genetics, and organization of medical service is impossible without knowledge of mathematics. Unfortunately, along with the evident importance of mathematical preparation for a medical profession, its need is poorly realized not only by junior students, but even by some teachers of specialized departments of medical schools.The aim of the publication is to discuss the problems that arise in the teaching of mathematical disciplines to students at a medical school and to suggest possible solutions to these problems.Methodology and research methods. The study is based on the use of modeling of the educational process. The methods of analysis, generalization and the method of expert assessments were applied in the course of the research.Results and scientific novelty. The aspects of mathematical preparation at the university are considered on the basis of the application of the multiplicative model of training quality. It is shown that the main students' learning difficulties in Mathematics are connected with the following factors: the initial level of mathematical preparation of students and their motivation; outdated methods of Mathematics teaching and academic content designing which is being complicated by existing imbalance between the amount of training material and time frame for its studying. The authors suppose that it is possible to improve the quality of education through the increase or redistribution of the number of teaching hours; stimulation students' motivation; enhancement of content and methodical components of teaching by means of active use of electronic resources and information technologies. Teachers should aspire to avoid excessive mathematical formalism as well to form in students the skills of independent work through the use of mathematical and computer methods.Practical significance. The authors come to the conclusion that the transition from traditional teaching to the teaching through the technological application of mathematical methods in medical practice and independent conduction of medical research is required for improvement the quality of Mathematics teaching of future physicians.